2019
DOI: 10.1038/s41598-019-39184-4
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of spinal Trpv1 attenuates neuropathic pain in rats by inhibiting CAMKII expression and ERK2 phosphorylation

Abstract: Accumulating evidence suggests a potential role of transient receptor potential vanilloid 1 (TRPV1) channels in inflammatory and cancer-related pain. However, the role of TRPV1 in the maintenance of neuropathic pain remains elusive. The current study investigated the effects of transient Trpv1 gene silencing using a small interference RNA (siRNA) on neuropathic pain induced by chronic constriction injury (CCI) of the sciatic nerve in rats. Seven days after CCI, the TRPV1 siRNA was intrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 68 publications
(72 reference statements)
2
21
0
Order By: Relevance
“…Recent reports suggest that neuropathic pain increases TRPV1 expression, as well as the Ca 2+ /calmodulin‐dependent protein kinase II (CAMKII) and extracellular signal‐regulated kinase (ERK) phosphorylation. These data confirm that there is a up phosphorylation (sensitization) of TRPV1 receptors on neuropathic condition 59 . In line with this, one of the acute desensitization theories suggest that protein kinase C (PKC) phosphorylates or sensitizes TRPV1 receptors; this sensitization occurs when the receptor is binding to analogues as capsaicin.…”
Section: Discussionsupporting
confidence: 72%
“…Recent reports suggest that neuropathic pain increases TRPV1 expression, as well as the Ca 2+ /calmodulin‐dependent protein kinase II (CAMKII) and extracellular signal‐regulated kinase (ERK) phosphorylation. These data confirm that there is a up phosphorylation (sensitization) of TRPV1 receptors on neuropathic condition 59 . In line with this, one of the acute desensitization theories suggest that protein kinase C (PKC) phosphorylates or sensitizes TRPV1 receptors; this sensitization occurs when the receptor is binding to analogues as capsaicin.…”
Section: Discussionsupporting
confidence: 72%
“…Guo et al showed an increase in CAMKII, TRPV1 and pERK1/2 protein levels in the spinal dorsal horn of animals suffering from chronic pain. Moreover, silencing of the TRPV1 gene attenuated mechanical and thermal hyperalgesia and CaMKII and ERK2 phosphorylation [ 25 ]. On the other hand, CaMKII is required for TRPV1 ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of pain does not always correlate with the extent of joint damage or presence of active inflammation, we investigated the occurrence of a central component of OA pain by correlating OA pain behavior of the animals reported in the previous studies [ 24 ] with the assessment of ATF-3, a marker of spinal neuronal activity. Involvement of mitogen-activated protein kinases 3 and 14 (MAPK3 and MAPK14, respectively) in the chronic pain formation has been shown in preclinical studies [ 25 , 26 ]. Furthermore, the present investigation aimed to examine the spinal and joint endocannabinoid systems in combination with TRPV1 and its sensitization factors during pain development in a rat sodium monoiodoacetate (MIA) model of OA.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in a spinal nerve ligation model, TRPV1 mRNA expression increased in DRG neurons up to 4 weeks after injury [13]. A study on chronic constriction injuries of the sciatic nerve reported increased TRPV1 protein in the spinal dorsal horn and DRG 1 week after injury [48]. Another study using a chronic constrictive spinal nerve injury model reported increased TRPV1 protein in the spinal cord at 1 and 2 weeks after injury [14].…”
Section: Modulation Of Trpv1 Channel Expression Under Np Conditionsmentioning
confidence: 97%